Psychological foundations of dynamic capabilities: reflexion and reflection in strategic management - Hodgkinson, Gerard P.; Healey, Mark P. (Strategic management journal, 2011)
In recent years, there has been a move to identify the behavioral foundations underpinning the evolutionary and economic fitness of the enterprise. Indeed, the dynamic capabilities project now occupies center stage in the field of strategic management. Yet the accounts developed thus far—like much of the field's theory and research more generally—are predicated upon a cold cognition logic that downplays the significance of emotional/affective and nonconscious cognitive processes for strategic adaptation. In this article, we rectify this imbalance by drawing upon contemporary advances in social cognitive neuroscience and neuroeconomics to develop a series of countervailing insights and new prescriptions for the development of dynamic capabilities. Using Teece's (2007) influential framework to organize and illustrate our arguments, we demonstrate how the fundamental capabilities of sensing, seizing, and transforming each require firms to harness the cognitive and emotional capacities of individuals and groups to blend effortful forms of analysis with the skilled utilization of less deliberative, intuitive processes.